Evaluating diversity, equity, and inclusion consultation requests. Issue 9 (September 2022) - Fernandez, Aileen I.; Starbird, Chrystal; Davis-Reyes, Brionna; Termini, Christina M.; Hinton, Antentor; McCall, Terika
Abstract : Diversity, equity, and inclusion (DEI) efforts have increased drastically as companies and institutions recognize their value in fostering innovative ideas for success. Individuals trained in these efforts can impart their knowledge and expertise in consultation, but this transaction should be mutually beneficial. Here, we provide recommendations to maximize consulting opportunities.